2(3z+1)-(z-6)=18

Simple and best practice solution for 2(3z+1)-(z-6)=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3z+1)-(z-6)=18 equation:


Simplifying
2(3z + 1) + -1(z + -6) = 18

Reorder the terms:
2(1 + 3z) + -1(z + -6) = 18
(1 * 2 + 3z * 2) + -1(z + -6) = 18
(2 + 6z) + -1(z + -6) = 18

Reorder the terms:
2 + 6z + -1(-6 + z) = 18
2 + 6z + (-6 * -1 + z * -1) = 18
2 + 6z + (6 + -1z) = 18

Reorder the terms:
2 + 6 + 6z + -1z = 18

Combine like terms: 2 + 6 = 8
8 + 6z + -1z = 18

Combine like terms: 6z + -1z = 5z
8 + 5z = 18

Solving
8 + 5z = 18

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 5z = 18 + -8

Combine like terms: 8 + -8 = 0
0 + 5z = 18 + -8
5z = 18 + -8

Combine like terms: 18 + -8 = 10
5z = 10

Divide each side by '5'.
z = 2

Simplifying
z = 2

See similar equations:

| -135+2x=52-9x | | .3x-.14x-.81=-.6x+.29 | | 66w+50= | | 9y+15=5y-5 | | X=2x-3+4 | | .3x-.14x-.81=-.6x+29 | | 6x-1=5+3x | | 2*12*40+5*18*40+3238+500= | | 2x-43=65 | | 33w+49-33w+1= | | 9+(-10)= | | 70=-14x | | 0.162+2.76= | | 6x-4+5=1 | | 2+11x+11K-3x-3k-9= | | -44-6n=4(-10-n) | | -8-0-(-16)-7+5= | | 6x^2+25x-24=0 | | 6y-11x=15 | | 15r^2-4r-4=0 | | -4=3b+b | | 2x+3-3x=7 | | (-4+-1x^2)=0 | | (2+5)*(12+18)*40+3238+500= | | .80x+2.30=30 | | 9x-5=1+6x | | 6m=-6+144 | | [21+(-21)]+[21+(-25)]= | | 10m-29=71whatsm | | 3w+8x-13y+6w+7x+8y= | | 10y=2x-13 | | ln(e^4*x)+8=0 |

Equations solver categories